2020
DOI: 10.1093/ejcts/ezaa183
|View full text |Cite
|
Sign up to set email alerts
|

Early outcomes in 147 consecutive cases of subxiphoid single-port thymectomy and evaluation of learning curves

Abstract: Abstract OBJECTIVES The aim of the present study was to examine some initial results and learning curves concerning subxiphoid single-port thymectomy (SSPT), thereby clarifying the safety of this surgical approach and describing the precautions for adopting it. METHODS Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 14 publications
1
13
1
Order By: Relevance
“…In contrast to the literature's overwhelming opinion that subxiphoid VATS results in much less early postoperative pain than intercostal VATS following thoracic surgery [12][13][14][15][16]18], our study found the subxiphoid incision produced more pain than the intercostal incision during the early postoperative period (POD-1, POD-2, and POD-Discharge), but only in the bilateral VATS group, not in the unilateral VATS group. The authors suggest one reason for the difference may be because the subxiphoid incision was always made below the xiphoid process and slightly tilted in the direction of the operative costal arch.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…In contrast to the literature's overwhelming opinion that subxiphoid VATS results in much less early postoperative pain than intercostal VATS following thoracic surgery [12][13][14][15][16]18], our study found the subxiphoid incision produced more pain than the intercostal incision during the early postoperative period (POD-1, POD-2, and POD-Discharge), but only in the bilateral VATS group, not in the unilateral VATS group. The authors suggest one reason for the difference may be because the subxiphoid incision was always made below the xiphoid process and slightly tilted in the direction of the operative costal arch.…”
Section: Discussioncontrasting
confidence: 99%
“…As can be seen in Table 1, males made up sixty-one percent and mean BMI was 23 kg/m 2 . Operative time, blood loss, complications, and postoperative hospital length-of-stay were comparable and similar to those reported in the subxiphoid VATS literature [12][13][14][15][16]. As can be seen in Supplemental table 1, out of the eleven patients receiving bilateral VATS, ve had primary spontaneous pneumothorax with contralateral blebs for which they received surgical treatments following previous reported procedures [24] and six had indeterminate lung nodules or suspected lung cancer and received simultaneous bilateral operations for accurate diagnosis and staging after weighing relative risks and bene ts.…”
Section: Resultssupporting
confidence: 81%
See 3 more Smart Citations